Laughter Contest in Traditional Russian Wedding of 19 - early 21 Centuries - M. G. Matlin (Научный диалог)
The author describes the experience of many years of work on the study of laughter in the Russian folk wedding. In this work, in particular, one of the forms of its embodiment in the Russian traditional and modern wedding is considered. Special attention is paid to such rites as Courtship, Visiting the groom’s house by girls, Ransoms in the bride’s house. It is shown that these and other wedding rites that require active interaction of the parties were very often at the same time laugh competitions, which clearly manifested mastery of such a type of folk eloquence, which is called balagurstvo . This competition, which was a dialogue, includes both spontaneous and stereotypical speech statements, in particular, such folklore genres as groomsman’s sayings and korilnye songs were replicas of the parties. The article proves that in the modern wedding this speech competition not only has been further developed and strengthened, but could already be implemented with the simultaneous use of oral and written speech, including official documents. Greater development in modern wedding also got not a verbal contest of parties, but action accompanying of humorous dialogue, which could use items having in the specific wedding situation a humorous meaning (for example, setting the table for guests by food waste instead of holiday treats).